1999
DOI: 10.1007/s100529900018
|View full text |Cite
|
Sign up to set email alerts
|

A critical phenomenological study of inclusive photon production in hadronic collisions

Abstract: We discuss fixed target and ISR inclusive photon production and attempt a comparison between theory and experiments. The dependence of the theoretical predictions on the structure functions, and on the renormalization and factorization scales is investigated. The main result of this study is that the data cannot be simultaneously fitted with a single set of scales and structure functions. On the other hand, there is no need for an additional intrinsic k T to force the agreement between QCD predictions and expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 17 publications
3
58
0
3
Order By: Relevance
“…[24] performed a systematic comparison of NLO calculations with most of the available photon results by 2006 (see also Refs. [25,26] for previous studies) and showed that collider isolated photon data was in reasonable agreement with the theoretical predictions. Indeed, as discussed in detail in [27], by (i) increasing the √ s from fixed-target to collider energies, and by (ii) requiring the photon to be isolated from any hadronic activity within a given distance around its direction, one is left with an isolated-photon sample dominated by energy scales away from non-perturbative effects (such as intrinsic-k T broadening [28]), and where the uncertain contribution from photons issuing from the collinear fragmentation of final-state partons [29] are significantly reduced.…”
Section: Introductionsupporting
confidence: 68%
“…[24] performed a systematic comparison of NLO calculations with most of the available photon results by 2006 (see also Refs. [25,26] for previous studies) and showed that collider isolated photon data was in reasonable agreement with the theoretical predictions. Indeed, as discussed in detail in [27], by (i) increasing the √ s from fixed-target to collider energies, and by (ii) requiring the photon to be isolated from any hadronic activity within a given distance around its direction, one is left with an isolated-photon sample dominated by energy scales away from non-perturbative effects (such as intrinsic-k T broadening [28]), and where the uncertain contribution from photons issuing from the collinear fragmentation of final-state partons [29] are significantly reduced.…”
Section: Introductionsupporting
confidence: 68%
“…The minimal baseline for a heavy-ion reaction constitutes the collision-number scaled expectation from proton-nucleon collisions. An accurate description thereof is still a matter of debate [4], so that we here employ empirical scaling relations in x t = 2q t / √ s, extracted from fits to data in Ref. [45].…”
Section: A Hard Photons and Thermal Fireball Evolutionmentioning
confidence: 99%
“…[3] for recent reviews). An identification of the QGP component in the spectra requires a reliable assessment of competing sources, most notably primordial production in hard nucleon-nucleon (N -N ) collisions [4], as well as the later hadronic emission. Owing to the vanishing invariant mass of real photons, all three sources generate essentially smooth spectra, measured as a function of transverse momentum, q t .…”
Section: Introductionmentioning
confidence: 99%
“…Several instrumental and analysis factors conspire to make this measurement relatively challenging: random pairing of a direct photon with a decay γ to give an invariant mass consistent with a π 0 ; two photons from a high-p T π 0 merging into a single cluster in the ECAL; and others. In addition, direct photons can also be produced by the collinear fragmentation of a hard quark or gluon (especially relevant at relatively low p T ) [234]. Thus their inclusive cross section can also (potentially) be affected by medium-induced attenuation [235], blurring their use as a clean calibration of the opposing jet.…”
Section: Z 0 -And γ *-Tagged Jet Studiesmentioning
confidence: 99%